A solid waste gelling material and its preparation method and application
By mixing high-titanium slag, vanadium-titanium converter steel slag and lime nitrogen and treating it through microwave plasma, combining desulfurization gypsum and alcohol amine compounds/cationic starch compound exciter, the low utilization rate of vanadium-titanium metallurgy and glue are solved. The problem of poor mechanical properties of coagulation materials has achieved efficient hydration and improved mechanical properties of solid waste gelling materials.
Patent Information
- Application Number
- CN202410720731.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-05
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-06-05
AI Technical Summary
Vanadium titanium metallurgical solid waste has low utilization rate in the prior art, and the mechanical properties of the obtained gelling materials are poor, especially when the TiO2 content in high titanium slag is ≥20%, its disadvantages are more obvious.
Vanadium-titanium metallurgy solid waste is generated by mixing high-titanium slag, vanadium-titanium converter steel slag and lime nitrogen, and processing it with microwave plasma. Then it is mixed with desulfurization gypsum and alcohol amine compounds/cationic starch compound exciter to improve the degree of hydration reaction and dispersion through charge adsorption and complexing.
It has improved the early strength and long-term strength of solid waste gelling materials, overcome the problem of poor mechanical properties caused by low activity of vanadium-titanium metallurgy, and made its performance comparable to ordinary silicate cement and is suitable for concrete production.
Smart Images

Figure CN118702422B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of solid waste resource utilization and building materials, and in particular to a solid waste gelling material and a preparation method and application thereof. Background Art
[0002] my country has rich reserves of vanadium-titanium magnetite, which are mainly concentrated in Sichuan and other regions. However, with the development of the metallurgical industry, the emission of vanadium-titanium metallurgical solid wastes such as high-titanium slag and vanadium-titanium converter slag has increased sharply, which not only occupies land resources but also pollutes the environment. Therefore, studying the resource utilization of vanadium-titanium metallurgical solid wastes has considerable economic significance and social benefits for the continuation of sustainable development of enterprises and environmental protection.
[0003] High-titanium slag is a granular or blocky waste slag obtained by quenching or naturally cooling the slag discharged from the smelting of pig iron using vanadium-titanium magnetite as raw material. Compared with ordinary blast furnace slag, high-titanium slag belongs to CaO-Al 2 O 3 -SiO 2 -TiO 2 The quaternary system contains TiO 2 The content is above 15%, and the CaO content is low, resulting in a high degree of polymerization of silicon-oxygen tetrahedron (glass) in high-titanium slag, poor grindability and low activity (the activity index is generally less than 60%, even if ground to a specific surface area of ≥400m 2 / kg, it is difficult to meet the requirements of S75 grade slag powder). When applied to cement concrete materials, the mechanical properties of cement concrete will be significantly reduced when the dosage reaches 10% or more, especially when the TiO 2 When the content is ≥20%, its disadvantages are more obvious.
[0004] Vanadium-titanium converter slag is a by-product of the steelmaking process. Taking the slag produced by Sichuan Desheng Group Vanadium Titanium Co., Ltd. as an example, its main components include CaO, SiO 2 , Fe 2 O 3 、Al 2 O 3 , MgO, etc. However, since the vanadium-titanium converter slag contains 1.5% to 2.0% V 2 O 5 and 1.0% to 3.0% TiO 2 , and also reduces the activity of vanadium-titanium converter slag, thus limiting its wide application.
[0005] At present, the resource utilization of vanadium-titanium metallurgical solid waste is mainly concentrated in cement mixed materials, mine filling cementitious materials, slag composite micropowders, etc. However, in these applications, vanadium-titanium metallurgical solid waste still has problems such as low utilization rate and poor mechanical properties of the obtained cementitious materials. At the same time, there is no report in the prior art on the application of high-titanium slag with a titanium dioxide weight content of ≥20wt% to prepare cementitious materials. Summary of the invention
[0006] In order to solve the above problems, the present invention provides a solid waste gelling material and a preparation method and application thereof.
[0007] In a first aspect, the present invention provides a solid waste gelling material, which comprises the following raw materials in parts by weight:
[0008] 78-89 parts of vanadium-titanium metallurgical solid waste, 10-20 parts of desulfurized gypsum and 1-3 parts of activator;
[0009] The vanadium-titanium metallurgical solid waste is obtained by mixing high-titanium slag with a titanium dioxide weight content of ≥20wt%, vanadium-titanium converter steel slag and lime nitrogen, and then treating with microwave plasma;
[0010] The activator is obtained by compounding an alcohol amine compound and a cationic starch.
[0011] Furthermore, the solid waste gelling material comprises the following raw materials in parts by weight:
[0012] 85.5 parts of vanadium-titanium metallurgical solid waste, 15 parts of desulfurized gypsum and 1.5 parts of activator;
[0013] The activator is obtained by compounding an alcohol amine compound and a cationic starch in a weight ratio of 100:(11-19);
[0014] The weight ratio of the high titanium slag, the vanadium titanium converter steel slag and the lime nitrogen is (40-50):(35-45):(7-13);
[0015] In terms of weight percentage, the weight content of titanium dioxide in the high-titanium slag is 20wt% to 25wt%.
[0016] Furthermore, the method for preparing vanadium-titanium metallurgical solid waste comprises the following process:
[0017] The high-titanium slag, the vanadium-titanium converter steel slag and the lime nitrogen are crushed and mixed to obtain a first mixed material;
[0018] The first mixed material is placed in a reaction chamber of a microwave plasma treatment device, which is open to atmospheric pressure and subjected to non-ionizing radiation treatment for 2 to 7 minutes under the conditions of microwave treatment power ≥ 1000 W and air as the working medium, to obtain the vanadium-titanium metallurgical solid waste.
[0019] Furthermore, the microwave processing power is 1100-1300W.
[0020] Furthermore, the alcoholamine compound includes at least one of triethanolamine and triisopropanolamine.
[0021] Furthermore, the cationic starch includes at least one of quaternary ammonium cationic starch, tertiary amine cationic starch, secondary amine cationic starch and primary amine cationic starch.
[0022] In a second aspect, the present invention provides a method for preparing the solid waste gelling material according to any one of the first aspects, the preparation method comprising the following steps:
[0023] Mixing vanadium-titanium metallurgical solid waste, desulfurized gypsum and an activator to obtain a second mixed material;
[0024] The second mixed material is added into a roller vertical mill for grinding to obtain the solid waste gelled material.
[0025] Further, the powder is ground to a specific surface area of ≥500m 2 / kg and the 30μm sieve residue is not more than 3.0%.
[0026] In a third aspect, the present invention provides a use of the solid waste cementitious material described in any one of the first aspect and the second aspect in the preparation of building materials.
[0027] In a fourth aspect, the present invention provides concrete, comprising a cementitious material, aggregate, admixture, additive and water; the cementitious material at least partially comprises the solid waste cementitious material described in any one of the first aspect and the second aspect.
[0028] The above technical solution provided by the embodiment of the present invention has at least the following advantages compared with the prior art:
[0029] The embodiment of the present invention provides a solid waste cementitious material, specifically a clinker-free solid waste-based cementitious material, in which no silicate cement clinker is added during the production process, and all raw materials are vanadium-titanium metallurgical solid waste and thermal power solid waste. The obtained solid waste cementitious material has performance comparable to that of ordinary silicate cement, and can replace cement in concrete production, providing a new means for the resource utilization of vanadium-titanium metallurgical solid waste. Specifically:
[0030] The invention mixes high-titanium slag, vanadium-titanium converter steel slag and lime nitrogen, and then performs microwave plasma treatment, so that the network structure of silicon-oxygen tetrahedron and aluminum-oxygen tetrahedron is destroyed, which is conducive to mutual excitation and synergistic hydration among the three raw materials of high-titanium slag, vanadium-titanium converter steel slag and desulfurized gypsum, so that the system continuously generates hydration products such as calcium vanadate (AFt) and CSH gel; at the same time, an activator obtained by compounding with an alcohol amine compound and cationic starch in an appropriate proportion is combined, and the dispersibility of the system materials and the degree of hydration reaction are promoted through charge adsorption dispersion effect and complexation, so as to improve the early strength and ensure the continuous growth of long-term strength, thereby overcoming the problem that the mechanical properties of the obtained cementitious material are poor due to the low activity of vanadium-titanium metallurgical solid waste such as high-titanium slag, so as to meet the use requirements of concrete production. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the invention and, together with the description, serve to explain the principles of the invention.
[0032] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.
[0033] Figure 1 A schematic flow chart of a method for preparing a solid waste gelling material provided in an embodiment of the present invention. DETAILED DESCRIPTION
[0034] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0035] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.
[0036] In a first aspect, the present invention provides a solid waste gelling material, which comprises the following raw materials in parts by weight:
[0037] 78-89 parts of vanadium-titanium metallurgical solid waste, 10-20 parts of desulfurized gypsum and 1-3 parts of activator;
[0038] The vanadium-titanium metallurgical solid waste is obtained by mixing high-titanium slag with a titanium dioxide weight content of ≥20wt%, vanadium-titanium converter steel slag and lime nitrogen, and then treating with microwave plasma;
[0039] The activator is obtained by compounding an alcohol amine compound and a cationic starch.
[0040] The embodiment of the present invention provides a solid waste cementitious material, specifically a clinker-free solid waste-based cementitious material, in which no silicate cement clinker is added during the production process, and all raw materials are vanadium-titanium metallurgical solid waste and thermal power solid waste. The obtained solid waste cementitious material has performance comparable to that of ordinary silicate cement, and can replace cement in concrete production, providing a new means for the resource utilization of vanadium-titanium metallurgical solid waste. Specifically:
[0041] The invention mixes high-titanium slag, vanadium-titanium converter steel slag and lime nitrogen, and then performs microwave plasma treatment, so that the network structure of silicon-oxygen tetrahedron and aluminum-oxygen tetrahedron is destroyed, which is conducive to mutual excitation and synergistic hydration among the three raw materials of high-titanium slag, vanadium-titanium converter steel slag and desulfurized gypsum, so that the system continuously generates hydration products such as calcium vanadate (AFt) and CSH gel; at the same time, an activator obtained by compounding with an alcohol amine compound and cationic starch in an appropriate proportion is combined, and the dispersibility of the system materials and the degree of hydration reaction are promoted through charge adsorption dispersion effect and complexation, so as to improve the early strength and ensure the continuous growth of long-term strength, thereby overcoming the problem that the mechanical properties of the obtained cementitious material are poor due to the low activity of vanadium-titanium metallurgical solid waste such as high-titanium slag, so as to meet the use requirements of concrete production.
[0042] In some specific embodiments, the solid waste gelling material includes the following raw materials in parts by weight:
[0043] 85.5 parts of vanadium-titanium metallurgical solid waste, 15 parts of desulfurization gypsum and 1.5 parts of activator.
[0044] In some specific embodiments, the weight ratio of the high titanium slag, the vanadium-titanium converter steel slag and the lime nitrogen is (40-50):(35-45):(7-13).
[0045] In some specific embodiments, the activator is obtained by compounding an alcohol amine compound and a cationic starch in a weight ratio of 100:(11-19).
[0046] In some specific embodiments, the titanium dioxide content in the high-titanium slag is 20 wt % to 25 wt %, calculated in weight percentage.
[0047] In some specific embodiments, the method for preparing vanadium-titanium metallurgical solid waste comprises the following process:
[0048] The high-titanium slag, the vanadium-titanium converter steel slag and the lime nitrogen are crushed and mixed to obtain a first mixed material;
[0049] The first mixed material is placed in a reaction chamber of a microwave plasma treatment device, which is open to atmospheric pressure and subjected to non-ionizing radiation treatment for 2 to 7 minutes under the conditions of microwave treatment power ≥ 1000 W and air as the working medium, to obtain the vanadium-titanium metallurgical solid waste.
[0050] In some specific embodiments, the microwave treatment power is 1100-1300W.
[0051] In some specific embodiments, the alcoholamine compound includes at least one of triethanolamine and triisopropanolamine.
[0052] In some specific embodiments, the cationic starch includes at least one of quaternary ammonium cationic starch, tertiary amine cationic starch, secondary amine cationic starch and primary amine cationic starch.
[0053] In some specific embodiments, lime nitrogen is a mixture of calcium cyanamide, calcium oxide and other insoluble impurities such as carbon (graphite), is gray-black in color, contains 20% to 22% nitrogen, has a special odor, and is often used as an alkaline fertilizer.
[0054] In a second aspect, based on the same inventive concept, the present invention provides a method for preparing the solid waste gelling material as described in any one of the first aspects, such as Figure 1 As shown, the preparation method comprises the following steps:
[0055] Mixing vanadium-titanium metallurgical solid waste, desulfurized gypsum and an activator to obtain a second mixed material;
[0056] The second mixed material is added into a roller vertical mill for grinding to obtain the solid waste gelled material.
[0057] In some specific embodiments, the grinding process is performed until the specific surface area of all components is ≥500m 2 / kg and the 30μm sieve residue is not more than 3.0%.
[0058] In a third aspect, based on the same inventive concept, the present invention provides the use of the solid waste cementitious material described in any one of the first aspect and the second aspect in the preparation of building materials.
[0059] In a fourth aspect, based on the same inventive concept, the present invention provides a concrete comprising cementitious material, aggregate, admixture, additive and water; the cementitious material at least partially comprises the solid waste cementitious material described in any one of the first aspect and the second aspect.
[0060] It should be noted that, in the solid waste gelling material and preparation method thereof provided in the embodiments of the present invention, the raw materials involved, unless otherwise specified or limited, can all be commercially available products. For example, cationic starch can be directly commercially available products sold by companies such as Guangdong Wengjiang Chemical Reagent Co., Ltd., Hubei Yamade Biomedicine Co., Ltd., and Wuhan Kmik Biomedicine Technology Co., Ltd., and its CAS registration number is 56780-58-6; at the same time, the process steps and parameters involved can be carried out according to the existing solid waste gelling material preparation process or using existing equipment in a conventional manner.
[0061] The present invention will be further described below in conjunction with specific examples. It should be understood that these examples are intended only to illustrate the present invention and are not intended to limit the scope of the present invention. The experimental methods in the following examples that do not specify specific conditions are usually measured according to national standards. If there is no corresponding national standard, then the conditions recommended by the manufacturer are followed.
[0062] The main raw material information involved in the following examples and comparative examples is as follows:
[0063] High titanium slag: Produced by Sichuan Desheng Group Vanadium Titanium Co., Ltd.; In terms of weight percentage, the main chemical components of high titanium slag include: TiO 2 24.66%, SiO 2 19.06%, Al 2 O 3 13.40%, MgO 8.64%, CaO 27.23%, MnO1.24%, Fe 2 O 3 2.50%, SO 3 1.31% and trace amounts of chemical elements, etc.; activity index <50%.
[0064] Vanadium-titanium converter slag: Produced by Sichuan Desheng Group Vanadium-Titanium Co., Ltd.; In terms of weight percentage, the main chemical components of vanadium-titanium converter slag include: SiO 2 8.64%, MgO 5.44%, CaO 52.91%, MnO 2.06%, TFe 9.13%, V 2 O 5 1.23%, TiO 2 1.30%, fCaO 17.87% and trace chemical elements, etc.
[0065] Desulfurized gypsum: Produced by Sichuan Desheng Group Vanadium Titanium Co., Ltd.; in terms of weight percentage, the main chemical components of desulfurized gypsum include: CaO 43.29%, SiO 2 4.07%, Fe 2 O3 1.89%, MgO 1.76%, Al 2 O 3 1.51%, SO 2 42.11%, NaO 1.18% and trace amounts of chemical elements, etc.
[0066] Cationic starch: a commercially available product with a CAS registration number of 56780-58-6.
[0067] Example 1
[0068] This example provides a solid waste gelling material, which includes the following raw materials in parts by weight:
[0069] 85.5 parts of vanadium-titanium metallurgical solid waste, 15 parts of desulfurized gypsum and 1.5 parts of activator;
[0070] The vanadium-titanium metallurgical solid waste is obtained by mixing high-titanium slag, vanadium-titanium converter steel slag and lime nitrogen, and then treating with microwave plasma; the weight ratio of the high-titanium slag, the vanadium-titanium converter steel slag and the lime nitrogen is 45.5:40:11;
[0071] The activator is obtained by compounding triethanolamine and cationic starch in a weight ratio of 100:13.
[0072] The method for preparing the solid waste gelling material comprises the following steps:
[0073] Step (1): crushing and mixing high-titanium slag, vanadium-titanium converter steel slag and lime nitrogen to obtain a first mixed material with a particle size of less than 2 mm; placing the first mixed material in a reaction chamber of a microwave plasma treatment device, using an atmospheric pressure open chamber, performing non-ionizing radiation treatment for 5 minutes under the conditions of a microwave treatment power of 1200 W and air as a working medium, and cooling to room temperature to obtain the vanadium-titanium metallurgical solid waste;
[0074] Step (2): mixing the vanadium-titanium metallurgical solid waste obtained in step (1), desulfurized gypsum and an activator to obtain a second mixed material;
[0075] Step (3): Add the second mixed material obtained in step (2) into a roller mill for grinding until the specific surface area of all components is 550 m 2 / kg and the 30μm sieve residue is not more than 3.0%, to obtain the solid waste gelling material.
[0076] Example 2
[0077] This example provides a solid waste gelling material, which includes the following raw materials in parts by weight:
[0078] 78 parts of vanadium-titanium metallurgical solid waste, 10 parts of desulfurized gypsum and 1 part of activator;
[0079] The vanadium-titanium metallurgical solid waste is obtained by mixing high-titanium slag, vanadium-titanium converter steel slag and lime nitrogen, and then treating with microwave plasma; the weight ratio of the high-titanium slag, the vanadium-titanium converter steel slag and the lime nitrogen is 40:35:7;
[0080] The activator is obtained by compounding triethanolamine and cationic starch in a weight ratio of 100:11.
[0081] The method for preparing the solid waste gelling material comprises the following steps:
[0082] Step (1): crushing and mixing high-titanium slag, vanadium-titanium converter steel slag and lime nitrogen to obtain a first mixed material with a particle size of less than 2 mm; placing the first mixed material in a reaction chamber of a microwave plasma treatment device, using an atmospheric pressure open chamber, performing non-ionizing radiation treatment for 7 minutes under the conditions of a microwave treatment power of 1100 W and air as a working medium, and cooling to room temperature to obtain the vanadium-titanium metallurgical solid waste;
[0083] Step (2): mixing the vanadium-titanium metallurgical solid waste obtained in step (1), desulfurized gypsum and an activator to obtain a second mixed material;
[0084] Step (3): Add the second mixed material obtained in step (2) into a roller mill for grinding until the specific surface area of all components is 535 m 2 / kg and the 30μm sieve residue is not more than 3.0%, to obtain the solid waste gelling material.
[0085] Example 3
[0086] This example provides a solid waste gelling material, which includes the following raw materials in parts by weight:
[0087] 89 parts of vanadium-titanium metallurgical solid waste, 20 parts of desulfurized gypsum and 2 parts of activator;
[0088] The vanadium-titanium metallurgical solid waste is obtained by mixing high-titanium slag, vanadium-titanium converter steel slag and lime nitrogen, and then treating with microwave plasma; the weight ratio of the high-titanium slag, the vanadium-titanium converter steel slag and the lime nitrogen is 50:45:13;
[0089] The activator is obtained by compounding triethanolamine and cationic starch in a weight ratio of 100:18.
[0090] The method for preparing the solid waste gelling material comprises the following steps:
[0091] Step (1): crushing and mixing high-titanium slag, vanadium-titanium converter steel slag and lime nitrogen to obtain a first mixed material with a particle size of less than 2 mm; placing the first mixed material in a reaction chamber of a microwave plasma treatment device, using an atmospheric pressure open chamber, performing non-ionizing radiation treatment for 2 minutes under the conditions of a microwave treatment power of 1300 W and air as a working medium, and cooling to room temperature to obtain the vanadium-titanium metallurgical solid waste;
[0092] Step (2): mixing the vanadium-titanium metallurgical solid waste obtained in step (1), desulfurized gypsum and an activator to obtain a second mixed material;
[0093] Step (3): Add the second mixed material obtained in step (2) into a roller mill for grinding until the specific surface area of all components is 540 m 2 / kg and the 30μm sieve residue is not more than 3.0%, to obtain the solid waste gelling material.
[0094] Comparative Example 1
[0095] This example provides a solid waste cementitious material and a preparation method thereof, which differs from Example 1 only in that: the microwave plasma treatment in step (1) is adjusted to microwave treatment, specifically: high-titanium slag, vanadium-titanium converter steel slag and lime nitrogen are crushed and mixed to obtain a first mixture with a particle size of less than 2 mm; the first mixture is treated under a microwave treatment power of 1200 W for 5 minutes, and cooled to room temperature to obtain the vanadium-titanium metallurgical solid waste; the remaining steps and parameters are the same.
[0096] Comparative Example 2
[0097] This example provides a solid waste cementitious material and a preparation method thereof, which differs from Example 1 only in that: the amount of lime nitrogen in step (1) is adjusted to 0 (i.e., no lime nitrogen is added), specifically: high-titanium slag and vanadium-titanium converter slag are crushed and mixed to obtain a first mixed material with a particle size of less than 2 mm; the first mixed material is placed in a reaction chamber of a microwave plasma treatment equipment, and is opened at atmospheric pressure, subjected to non-ionizing radiation treatment for 5 minutes under the conditions of a microwave treatment power of 1200 W and air as the working medium, and cooled to room temperature to obtain the vanadium-titanium metallurgical solid waste; the remaining steps and parameters are the same.
[0098] Comparative Example 3
[0099] This example provides a solid waste cementitious material and a preparation method thereof, which differs from Example 1 only in that the weight ratio of the high-titanium slag, the vanadium-titanium converter steel slag and the lime nitrogen in step (1) is adjusted to 45.5:40:30; the remaining steps and parameters are the same.
[0100] Comparative Example 4
[0101] This example provides a solid waste gelling material and a preparation method thereof, which is different from Example 1 only in that the amount of cationic starch used is 0 (ie, the activator is an alcohol amine compound); the remaining steps and parameters are the same.
[0102] Test Case
[0103] In this example, the mortar strength test was carried out on the solid waste cementitious materials obtained in the above embodiments and comparative examples in accordance with the standard GB / T 17671-2021 "Test method for cement mortar strength (ISO method)". The compressive strength test results at 3d, 7d and 28d are shown in Table 1.
[0104] Table 1
[0105] Test samples 3d compressive strength (MPa) 7d compressive strength (MPa) 28d compressive strength (MPa) Example 1 23.1 36.8 55.3 Example 2 18.2 26.4 43.0 Example 3 20.5 29.1 46.7 Comparative Example 1 7.3 15.7 24.9 Comparative Example 2 5.6 11.3 20.4 Comparative Example 3 7.9 16.8 28.5 Comparative Example 4 6.8 14.5 22.3
[0106] It can be seen from Table 1 that: 1) The performance of the solid waste cementitious material provided by Examples 2 to 3 of the present invention is equivalent to the strength grade of 42.5 ordinary Portland cement (3d compressive strength ≥17.0Mpa, 28d compressive strength ≥42.5Mpa), and the performance of the solid waste cementitious material provided by Example 1 is better, reaching the strength grade of 42.5R ordinary Portland cement (3d compressive strength ≥22.0Mpa, 28d compressive strength ≥42.5Mpa), and can replace cement in concrete production; 2) Compared with Comparative Examples 1 to 3, the performance advantage of the solid waste cementitious material provided by the embodiments of the present invention is more significant, indicating that the present invention is prepared by mixing high-titanium slag, vanadium-titanium converter slag and lime nitrogen, and then treating them with microwave plasma, and compounding them with alcohol amine compounds and cationic starch to obtain an activator. The two cooperate with each other and overcome the problem of poor mechanical properties of the obtained cementitious material due to the low activity of vanadium-titanium metallurgical solid waste such as high-titanium slag.
[0107] In addition, high-titanium slag (compared with the high-titanium slag in Example 1, the only difference is that no lime nitrogen and microwave plasma treatment are added) was added to 42.5 grade ordinary Portland cement at a dosage of 45.5% as a basic control, and then the mortar strength test was carried out according to the same test method as above. The test results showed that the mechanical properties of the mortar were significantly reduced, and the 7d compressive strength and 28d compressive strength were 8.2MPa and 15.4MPa, respectively.
[0108] In summary, the embodiments of the present invention provide a solid waste cementitious material and a preparation method and application thereof. The solid waste cementitious material is specifically a clinker-free solid waste-based cementitious material. No silicate cement clinker is added during its production process. All raw materials are vanadium-titanium metallurgical solid waste and thermal power solid waste. The obtained solid waste cementitious material has performance comparable to that of ordinary silicate cement, can replace cement in concrete production, and provides a new means for resource utilization of vanadium-titanium metallurgical solid waste.
[0109] Various embodiments of the present invention may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present invention; therefore, the range description should be considered to have specifically disclosed all possible sub-ranges and single numerical values within the range. For example, the range description from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.
[0110] The foregoing is merely a specific embodiment of the present invention, which enables those skilled in the art to understand or implement the present invention. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features claimed herein.
Claims
1. A solid waste gelling material, characterized in that: The solid waste gelling material includes the following raw materials in parts by weight: 78-89 parts of vanadium-titanium metallurgical solid waste, 10-20 parts of desulfurized gypsum and 1-3 parts of activator; The vanadium-titanium metallurgical solid waste is obtained by mixing high-titanium slag with a titanium dioxide weight content of ≥20wt%, vanadium-titanium converter steel slag and lime nitrogen, and then treating with microwave plasma; The weight ratio of the high titanium slag, the vanadium titanium converter steel slag and the lime nitrogen is (40-50): (35-45): (7-13); The activator is obtained by compounding an alcohol amine compound and a cationic starch.
2. The solid waste gelling material according to claim 1, characterized in that: The solid waste gelling material includes the following raw materials in parts by weight: 85.5 parts of vanadium-titanium metallurgical solid waste, 15 parts of desulfurized gypsum and 1.5 parts of activator; The activator is obtained by compounding an alcohol amine compound and a cationic starch in a weight ratio of 100:(11-19); In terms of weight percentage, the weight content of titanium dioxide in the high-titanium slag is 20wt%~25wt%.
3. The solid waste gelling material according to claim 1, characterized in that: The preparation method of the vanadium-titanium metallurgical solid waste The process includes: The high-titanium slag, the vanadium-titanium converter steel slag and the lime nitrogen are crushed and mixed to obtain a first mixed material; The first mixed material is placed in a reaction chamber of a microwave plasma treatment device, which is open to atmospheric pressure and subjected to non-ionizing radiation treatment for 2 to 7 minutes under the conditions of microwave treatment power ≥ 1000 W and air as the working medium, to obtain the vanadium-titanium metallurgical solid waste.
4. The solid waste gelling material according to claim 3, characterized in that: The microwave treatment power is 1100-1300W.
5. The solid waste gelling material according to claim 1, characterized in that: The alcoholamine compound includes at least one of triethanolamine and triisopropanolamine.
6. The solid waste gelling material according to claim 1, characterized in that: The cationic starch includes at least one of quaternary ammonium type cationic starch, tertiary amine type cationic starch, secondary amine type cationic starch and primary amine type cationic starch.
7. A method for preparing a solid waste gelling material according to any one of claims 1 to 6, characterized in that: The preparation method comprises the following steps: Mixing vanadium-titanium metallurgical solid waste, desulfurized gypsum and an activator to obtain a second mixed material; The second mixed material is added into a roller vertical mill for grinding to obtain the solid waste gelled material.
8. The method for preparing solid waste gelling material according to claim 7, characterized in that: Grind to a specific surface area of ≥500m 2 / kg and the residue on 30μm sieve is not more than 3.0%.
9. Use of the solid waste gelling material according to any one of claims 1 to 6 or the solid waste gelling material prepared by the method for preparing the solid waste gelling material according to any one of claims 7 to 8 in preparing building materials.
10. A concrete, characterized in that: The concrete comprises cementitious materials, aggregates, admixtures, additives and water; the cementitious materials at least partially comprise the solid waste cementitious materials described in any one of claims 1 to 6 or the solid waste cementitious materials prepared by the method for preparing the solid waste cementitious materials described in any one of claims 7 to 8.
Citation Information
Patent Citations
A Method for Preparing Cementitious material with all solid wasteContaining Refining Slag
AU2020101223A4
Method for preparing unfired cement by using concrete waste residue
CN113354313A